Transformation Toward What End? Exploring Later Life Learning in Community Volunteering - Miya Narushima (Adult Education Research Conference, 2000)
A qualitative study of 15 older volunteers in Toronto details how informal learning takes place in community volunteering, and urges the expansion of the concept of later life education during an era of increasing longevity and languishing welfare support